2022
DOI: 10.1080/17482631.2022.2103934
|View full text |Cite
|
Sign up to set email alerts
|

Possible paths to increase detection of child sexual abuse in child and adolescent psychiatry: a meta-synthesis of survivors’ and health professionals’ experiences of addressing child sexual abuse

Abstract: Background Efforts are directed both towards prevention and early detection of Child sexual abuse (CSA). Yet, only about 50% of CSA survivors disclose before adulthood, and health professionals rarely are the first disclosure recipients. Increasing the detection rate of CSA within the context of Child and Adolescent Psychiatry (CAP) therefore represents a significant secondary prevention strategy. However, facilitating CSA disclosure when the survivor is reluctant to tell is a highly complex and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
3
9
0
Order By: Relevance
“…The results highlight the complexity of uncovering CSA and emphasise some of the challenges healthcare professionals and CAP institutions must resolve, to enable the young person to disclose CSA experiences. The results align with and expand existing knowledge of how healthcare professionals conduct this demanding clinical task and what might facilitate this work (Stige et al 2022 ). The current data is not sufficient to provide conclusive answers, but our results do reveal some important dilemmas and potential areas of development to increase CSA detection rates in CAP.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results highlight the complexity of uncovering CSA and emphasise some of the challenges healthcare professionals and CAP institutions must resolve, to enable the young person to disclose CSA experiences. The results align with and expand existing knowledge of how healthcare professionals conduct this demanding clinical task and what might facilitate this work (Stige et al 2022 ). The current data is not sufficient to provide conclusive answers, but our results do reveal some important dilemmas and potential areas of development to increase CSA detection rates in CAP.…”
Section: Discussionsupporting
confidence: 83%
“…The survey was developed for this study and consisted of 10 questions mapping demographics and professional background, and 18 questions mapping assessment practice and experience of assessing CSA. The questions were developed on the basis of previous research (Albaek et al 2018 ; Gawel et al 2015 ; Nouman et al 2020 ; Stige et al 2022 ) and our own clinical experience. Ratings were given on a scale of 1–5 (low-high/rarely-frequently).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 25 years, research has identified numerous reasons as to why practitioners are reticent to address CSA in those presenting with mental health problems. Reasons for reticence are complex, but include lack of knowledge; low level of interpersonal skills, discomfort in asking about and addressing disclosure of sexual abuse; fear of retraumatization, time and resource constraints; adherence to the medical model, beliefs and attitudes regarding sexual abuse and its place in relation to mental health problems; believing CSA is the concern of 'other' specialists, and a practitioner's own experiences with CSA (Kennedy et al 2021;Stige et al 2022;Walsh et al 2022;Warne & McAndrew 2005). These barriers perpetuate CSA not being addressed at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, over a prolonged period, mental health professionals, such as nurses and psychiatrists, have been disinclined to routinely enquire about sexual abuse histories for numerous reasons; lack of confidence in how to ask and effectively respond, poor understanding and knowledge of CSA, and fear of reopening traumatic experiences (Dorahy & Clearwater 2012;Walsh et al 2022). Practitioners' avoidance of addressing CSA appears common throughout mental health care, including Child and Adolescent Mental Health Services (CAMHS) and male and female acute services (Kennedy et al 2021;Stige et al 2022;Walsh et al 2022;Warne & McAndrew 2005). Such lack of professional preparedness and/or willingness to address CSA could add to the distress and compromise the recovery of those they are providing care for.…”
Section: Csa and Mental Healthmentioning
confidence: 99%